(untitled) (Research, Society and Development, 2022)
Honey is a natural sweetener obtained by metabolic processes in the bee’s organism that transform the nectar and sugary secretions of vegetables into a supersaturated solution of sugars with a pleasant aroma and variable flavor. Although it is an expanding product in the Brazilian consumer market, much of its use is based on the empirical knowledge of the population and its processing in many regions is still carried out through rudimentary techniques, which makes it susceptible to adulteration and contamination. In this sense, it is essential to certify their suitability for human consumption, thus contributing to the nutritional security of the population. Therefore, the present study aimed to carry out the physicochemical characterization in honeys of the genus Apis sp. and Melipona sp. from the municipality of Cachoeira do Arari - PA. Thirty samples of honey were collected, fifteen from stinging bees and fifteen from stingless bees. The following results were obtained for the physicochemical parameters: dark amber color for 77% of the samples, pH from 3.06 to 3.99, free acidity from 43.06 to 186.79 meq.kg-1, humidity of 20.0 to 26.74%, ash from 0.02 to 0.58%, reducing sugars from 47.75 to 88.89%. The values ​​for PCA highlighted that the main responsible for separating the largest group with similar samples were ash, color and pH. In addition, the honey samples showed the need for care during the processing phases, as some physical-chemical parameters were in disagreement with current legislation.